Assessment of BTEX, PM10, and PM2.5 Concentrations in Nakhon Pathom, Thailand, and the Health Risks for Security Guards and Copy Shop Employees - Navaporn Kanjanasiranont (Atmosphere)
Concentrations of PM10, PM2.5, and the BTEX chemical group were studied in Nakhon Pathom, Thailand. The occupational health risk for workers (security guards and printing machine operators) was estimated against exposure to these pollutants. The average levels of PM10, PM2.5, and BTEX (benzene, toluene, ethylbenzene, and xylenes) were 67.32, 40.21, and 80.93 µg/m3, respectively. Among the BTEX group, toluene was the most prevalent at all the sampling sites, with mean levels of 55.71 µg/m3. The measured toluene/benzene ratios (T/B) indicated that the potential sources of BTEX at EG, CP1, and CP2 sites were influenced by vehicular or traffic sources. The level of benzene was utilized for evaluating the risk of cancer, whereas toluene and PM2.5 were estimated for non-cancer health risk. According to the health risk assessment (at the 95% CI), security guards tended to have higher cancer risk values due to benzene (4.04 × 10−5) when compared to printing machine operators (2.41 × 10−5) due to their frequent exposure to particular sources of high concentration. Meanwhile, the non-cancer risk values were at an acceptable level for security guards and copy center employees. In order to lower the overall cancer risk levels of workers, the most effective method is to reduce the chemical concentration.